2022
DOI: 10.23960/jsl.v10i3.596
|View full text |Cite
|
Sign up to set email alerts
|

The Mangrove Density, Diversity, and Environmental Factors as Important Variables to Support the Conservation Program of Essential Ecosystem Area in Muara Kali Ijo, Pantai Ayah, Kebumen

Abstract: The planning of wetland essential ecosystem area (EEA) conservation and preservation activities is important to support ecosystem stability, including the mangrove ecosystem. These activities should consider the ecological, economic, and social aspects. This study aimed to analyze the indicator of the mangrove ecosystem to support the planning program of  EEA conservation in Muara Kali Ijo, Pantai Ayah, Kebumen. The research method used the mapping and planning analysis of the EEA conservation program using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…This mangrove forest is close to the popular Logending Beach, giving Ayah Mangrove Forest the potential to be developed as an ecotourism attraction. A previous study documented various species in Ayah Mangrove Forest, including Rhizophora mucronata, Sonneratia caseolaris, Avicenna marina, Rhizophora apiculata, Acanthus ebracteatus, Acrostichum aureum, Bruguilera gymnorrhiza, and Nypa fruticans (Murniasih et al 2022). Among such species, R. mucronata dominated the vegetation community due to its rapid regeneration, giving the species a large forest cover which is essential in protecting the coastal area in Ayah Beach.…”
Section: Introductionmentioning
confidence: 99%
“…This mangrove forest is close to the popular Logending Beach, giving Ayah Mangrove Forest the potential to be developed as an ecotourism attraction. A previous study documented various species in Ayah Mangrove Forest, including Rhizophora mucronata, Sonneratia caseolaris, Avicenna marina, Rhizophora apiculata, Acanthus ebracteatus, Acrostichum aureum, Bruguilera gymnorrhiza, and Nypa fruticans (Murniasih et al 2022). Among such species, R. mucronata dominated the vegetation community due to its rapid regeneration, giving the species a large forest cover which is essential in protecting the coastal area in Ayah Beach.…”
Section: Introductionmentioning
confidence: 99%
“…The Brackish water culture is divided into two different systems, monoculture and polyculture (Cochard, 2017;Hu et al, 2020;Zhu et al, 2022;Jansen et al, 2023). Additionally, brackish water aquaculture can be carried out in areas with abundant natural food sources, such as estuaries and mangrove ecosystems (Duncan et al, 2016;Hilmi et al, 2021b, a;Soedibya et al, 2021;Murniasih et al, 2022). The development of a brackish water polyculture system enhances fish productivity per unit area and maintain water quality (Ekasari et al, 2015;Rose et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A brackish water polyculture is an aquaculture system between two or more fish species or aquatic organisms, such as milkfish and prawn or shrimp polyculture (Soedibya 2013;Rachmawati and Samidjan 2014;Nuryanto et al, 2017;Soedibya et al, 2017). Some research reported polyculture between Milkfish and Nile Tilapia (Soedibya, 2013;Mutia et al, 2018;Muyot et al, 2018), while others described a polyculture between prawn or shrimp and Nile Tilapia in brackish water (Mutia et al, 2018;Prabu et al, 2019;Hilmi et al, 2021bHilmi et al, , 2022Murniasih et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The wetland ecosystem is where many living things live, including giving benefits to the people. One important wetland ecosystem is a mangrove forest (Murniasih et al 2022). Mangrove forests are unique in many ways, such as carbon and nutrient cycles, typical of soil, and affected by tides.…”
Section: Introductionmentioning
confidence: 99%